DNA tests for maternity determination - Calacal, Gayvelline C.; Salvador, Jazelyn M.; Tabbada, Kristina A.; Franco, Shiela Ann Edith L.; Maiquilla, Sheena Marie B.; Sagum, Minerva S.; De Ungria, Maria Corazon A.
This report describes the use of DNA analysis in resolving two cases of maternity disputes involving inheritance claims of an alleged child. In the first case, genetic comparisons of the 15 autosomal Short Tandem Repeat DNA (aSTR-DNA) profiles of a deceased woman, brother and the alleged child of the deceased confirmed that the woman is the sibling of her brother but disproved a maternal relationship with the alleged child. In the other case, mtDNA analysis was used to refute the matrilineal relationship between the person claiming to be the child of the deceased and a sister of the deceased. (Author)
in: Acta Medica Philippina, 2008 vol 42 (2) pages: 39-41
Keywords: Forensic Genetics; DNA Fingerprinting; Microsatellite Repeats; Mitochondria; DNA Typing